Application of Hölder Function to Expansion Intensity of Spatial Phenomena Analysis - Mastalerz-Kodzis, Adrianna Damiana; Pośpiech, Ewa Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The development of methods describing time series using stochastic processes took place in the 20th century. Among others, stationary processes were modelled with Hurst exponent, whereas non‑stationary processes with Hölder function. The characteristic feature of this type of processes is the analysis of the memory present in the time series. At the turn of the 21st century interest in statistics and spatial econometrics, as well as analyses carried out within the new economic geography arose. In this article, we have proposed the implementation of methods taken from the analysis of time series in the modelling of spatial data and the application of selected measures in studying the intensity of expansion in spatial phenomena. As the intensity measure we use Hölder point exponents. The article is composed of two parts. The first one contains the description of study methodology, the second – examples of application.